1995
DOI: 10.1111/j.1432-1033.1995.209_1.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bile‐Salt‐Dependent Lipase with Membranes of Human Pancreatic Microsomes

Abstract: Immunolocalization studies indicated that, in contrast to other enzyme markers of human pancreatic secretion, bile-salt-dependent lipase (BSDL) was partly but specifically associated with endoplasmic reticulum membranes. In microsomes, temperature-induced phase separation using Triton X-I 14 elucidated the partition of BSDL between the aqueous phase and the detergent-rich phase containing hydrophilic and membrane proteins, respectively. The size of the membrane-associated BSDL (approx. 100 kDa) is compatible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 47 publications
7
39
0
Order By: Relevance
“…The immature, low molecular weight forms of both CEL variants co-distributed with a minor pool of p58 in the fast-sedimenting ER factions (fractions 6 -9). Moreover, they co-distributed with the ER chaperone GRP94 in agreement with the previously reported association of CEL with a GRP94-containing, membrane-bound, multiprotein folding complex (10,32). The somewhat wider distribution profile of CEL-MUT could indicate that this protein was more prone to associate with membranes intracellularly as well as extracellularly ( Fig.…”
Section: Cel-wt and Cel-mut Co-distribute With Markers Of The Early Ssupporting
confidence: 74%
See 1 more Smart Citation
“…The immature, low molecular weight forms of both CEL variants co-distributed with a minor pool of p58 in the fast-sedimenting ER factions (fractions 6 -9). Moreover, they co-distributed with the ER chaperone GRP94 in agreement with the previously reported association of CEL with a GRP94-containing, membrane-bound, multiprotein folding complex (10,32). The somewhat wider distribution profile of CEL-MUT could indicate that this protein was more prone to associate with membranes intracellularly as well as extracellularly ( Fig.…”
Section: Cel-wt and Cel-mut Co-distribute With Markers Of The Early Ssupporting
confidence: 74%
“…CEL is kept in close proximity to intracellular membranes during its transport from the endoplasmic reticulum (ER) to post-Golgi compartments in the acinar cells (10). Its membrane association is due to an interaction with a multiprotein complex that contains the chaperone GRP94 (glucose-regulated protein of 94 kDa) (11,12).…”
mentioning
confidence: 99%
“…Because genistein inhibits the formation and the release of cargo vesicles in the trans-Golgi network [47] one may suspect that the BSDL dissociates from the membrane folding complex in this latter compartment. This, in part, corroborates the fact that the membrane-associated BSDL was N-and O-glycosylated and appeared to be released from membranes after its glycosylation was completed in the trans-Golgi compartment [3,4]. Altogether, these results suggested that the dissociation of secretioncompetent molecules of BSDL from the folding complex occurs after the trans-Golgi compartment, probably in the transGolgi network, which is already known to segregate vesicle populations in cells [48].…”
Section: Discussionsupporting
confidence: 74%
“…BSDL molecules that cannot associate with Grp94 are unstable and cannot be secreted. Therefore Grp94 [3,4] may assist the sorting of BSDL towards the secretion pathway. Under these circumstances, the fraction of enzyme that does not associate with Grp94 (or with the folding complex) could be stored within the ER before entering another folding cycle, as described for folding mechanisms involving calnexin [40], and being targeted towards secretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation